2021
DOI: 10.3389/fphys.2021.695950
|View full text |Cite
|
Sign up to set email alerts
|

HR Max Prediction Based on Age, Body Composition, Fitness Level, Testing Modality and Sex in Physically Active Population

Abstract: Maximal heart rate (HRmax) is associated mostly with age, but age alone explains the variance in HRmax to a limited degree and may not be adequate to predict HRmax in certain groups. The present study was carried out on 3374 healthy Caucasian, Polish men and women, clients of a sports clinic, mostly sportspeople, with a mean age of 36.57 years, body mass 74.54 kg, maximum oxygen uptake (VO2max, ml∗kg–1∗min–1) 50.07. Cardiopulmonary exercise tests (CPET) were carried out on treadmills or cycle ergometers to eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…We may suspect that the difference in the younger population would be better explained by other factors, perhaps by training volume in cycling or running, which were not evaluated in this study. It is also possible that the differences in BC, especially FFM, reflect differences in cardiovascular function, which might play a more important role in older triathletes and could have a different importance in cycle ergometry and treadmill testing [ 56 , 57 ]. Differences in HRmax were significantly explained by BMI and FATP in the older population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We may suspect that the difference in the younger population would be better explained by other factors, perhaps by training volume in cycling or running, which were not evaluated in this study. It is also possible that the differences in BC, especially FFM, reflect differences in cardiovascular function, which might play a more important role in older triathletes and could have a different importance in cycle ergometry and treadmill testing [ 56 , 57 ]. Differences in HRmax were significantly explained by BMI and FATP in the older population.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in HRmax were significantly explained by BMI and FATP in the older population. It has previously been shown that HRmax is related to BC and BMI, but it remains unclear what the cause for this relationship is or why BC is related to the differences in HRmax between treadmill and cycle ergometry [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Usually, the modality of testing for CPET is chosen according to the dominant type of exercise performed by the athletes, i.e., treadmill (TE) for runners or cycle ergometer (CE) for cyclists. Results of CPET may vary considerably, depending on the chosen testing modality, likely due to different training experience, muscle activation patterns, and the static component in cycling [4][5][6][7]. A unique challenge is posed by duathletes and triathletes, who train in multiple disciplines, including both cycling and running.…”
Section: Introductionmentioning
confidence: 99%
“…They could end the protocol at any moment if felt they had reached their maximum. To ensure that participants achieved maximal effort, only those who's met ≥4 the following criteria were included: (1) RER ≥1.10, (2) presented VO 2 plateau (a VO 2 growth <100 ml min −1 with increasing speed/power), (3) f R >45 min −1 , and (4) declared exertion ≥18 according to the Borg scale, (5) highest achieved HR ≤ 15 bpm under predicted HR max (Lach et al, 2021). The exercises were terminated externally if VO 2 or HR no further increase with increasing speed or power.…”
Section: Cpet Protocolmentioning
confidence: 99%